Human cytomegalovirus and risk of incident cardiovascular disease in United Kingdom Biobank - Hamilton, EM; Allen, NE; Mentzer, AJ; Littlejohns, TJ (Oxford University Press, 2022)
Background Previous studies have yielded conflicting results on the association between human cytomegalovirus (HCMV) and cardiovascular disease (CVD). This study examined associations between HCMV and incident CVD, ischaemic heart disease (IHD) and stroke.